2019
DOI: 10.1111/ahe.12460
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and functional comparison of lingual papillae in suckling and adult feral cats: Forensic evidence

Abstract: Feral cats are considered as strays and are more likely to hunt in the street. We investigated the effect of environmental adaptations on the structures of lingual papillae in feral cats, which could be used as forensic evidence for their identification. There are no reported studies about the structural comparison of lingual papillae between suckling and adult feral cats. The present study described the lingual papillae of both suckling and adult cats macroscopically and microscopically via light and scanning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 37 publications
1
18
1
Order By: Relevance
“…33 The fungiform papillae were distributed in the middle and lateral-caudal regions of the dorsal surface, whose characteristics are similar to those described in the pig, 32 goat, 24 dog, 14 and paca. 40 The three-dimensional analysis demonstrated that the fungiform papilla was rounded and resembles a fungiform papilla type described for the Egyptian fruit bat, 21 but differs from the mushroom shape, 17,33 dome-like shape with varied sizes, 10 and the rectangular fungiform papillae. 21 After epithelium removal, the CTCs have a bud-flower shape and this differs from the volcano shape, 28 the rose-bud shape, 37 the handle shape, 41 the dome shape, 42 and the columnar shape.…”
Section: Figure 3 Transmission Electron Microscopy Of the Dorsal Epithelium Of The Tongue Of The Wild Boar A) The Epithelial Cells Of Thementioning
confidence: 86%
See 2 more Smart Citations
“…33 The fungiform papillae were distributed in the middle and lateral-caudal regions of the dorsal surface, whose characteristics are similar to those described in the pig, 32 goat, 24 dog, 14 and paca. 40 The three-dimensional analysis demonstrated that the fungiform papilla was rounded and resembles a fungiform papilla type described for the Egyptian fruit bat, 21 but differs from the mushroom shape, 17,33 dome-like shape with varied sizes, 10 and the rectangular fungiform papillae. 21 After epithelium removal, the CTCs have a bud-flower shape and this differs from the volcano shape, 28 the rose-bud shape, 37 the handle shape, 41 the dome shape, 42 and the columnar shape.…”
Section: Figure 3 Transmission Electron Microscopy Of the Dorsal Epithelium Of The Tongue Of The Wild Boar A) The Epithelial Cells Of Thementioning
confidence: 86%
“…The presence of taste buds in the lower region of the wall of the groove has been described for the pig. 32 The foliate papilla does not present taste buds in suckling and adult feral cat individuals, 17 and the foliate papillae are not very developed in the Artiodactyla order. 30 The foliate papillae presented three to four pairs of epithelial folds, separated by irregular parallel grooves, located in the lateral-caudal margin of the tongue.…”
Section: Figure 3 Transmission Electron Microscopy Of the Dorsal Epithelium Of The Tongue Of The Wild Boar A) The Epithelial Cells Of Thementioning
confidence: 99%
See 1 more Smart Citation
“…Morphogenesis of the gustatory papillae was completed during the postnatal life of some animals especially that having a short gestational period, such as in; rabbit (Elnasharty et al, 2013; Nabil & Tawfiek, 2020), cat (Haddad et al, 2019), rat (Asar, Kocamaz, Demir, & Üstunel, 1996; Hosley & Oakley, 1987; Iwasaki et al, 2001), mice (Toprak & Yilmaz, 2016), hamster (Whitehead & Kachele, 1994), moreover Haddad et al (2019) added that, the papillae spreading in suckling cats are analogous to those detected in adult cats. However, their shapes are dissimilar from those of the corresponding papillae in adults.…”
Section: Discussionmentioning
confidence: 99%
“…The mammalian tongue has a characteristic structure of lingual papillae (Abumandour, 2014; El‐Mansi, Al‐Kahtani, & Abumandour, 2019; Iwasaki, 2002; Kobayashi, Jackowiak, Frackowiak, Yoshimura, & Kumakura, 2005; Massoud & Abumandour, 2019, 2020). (Abumandour, 2014; Abumandour & El‐Bakary, 2013b; Haddad et al, 2019) in rabbit, bat, and cats added that, there are strong adaptation between the lingual papillae development and feeding and mastication behaviour in suckling and adult feral cats.…”
Section: Introductionmentioning
confidence: 99%